Unhoming Pedagogies: Collaborative Wandering and Wondering with Literature. (9th August 2021) - Pollard, Natalie; Ashfield, Deborah; Jelley, Jasmin
Abstract: This collaborative article reflects on a set of shared practices that were inspired by a Year 3 undergraduate Literary Studies module, which took place in 2018. In co-teaching and learning on this module, the authors found their disciplinary and pedagogic norms unsettled and set adrift (unhomed). This article traces how their processes of working together – in and beyond the University classroom – stimulated a critique of the rational individualist principles which had unconsciously steered their learning and teaching practices until this point. The article includes case studies from the experiences of three students who took the module, and a narrative frame that speaks from the perspective of a collaborative 'we' (which includes students and 'teacher'). The article tests out writing practices which reorient the customary Humanist terms in which educational research is conducted, and which disrupt the objective voice in which pedagogical reflection is often narrated. From this vertiginous perspective, the article also considers the authors' particular entanglements with the cultural politics of the contemporary UK Higher Education Institution (HEI), and the role of unhomed Humanities teaching as part of the 21C University.